Prediction of Vocational Education Coursework Assessment Results Based on the Simulated Annealing Neural Network. (31st March 2022) - Gao, Yan; Tan, Aidi; Wei, Yanping
Abstract : In order to improve the predictive effect of vocational education assessment results and provide a reliable boundary assessment platform for vocational education, this paper uses the simulated annealing neural network algorithm to process vocational education assessment data. Moreover, this article uses the SA algorithm based on the simulated annealing fish school algorithm (SAFSA) in the local search in the later stage of the AFSA algorithm to help the AFSA algorithm jump out of the local optimal solution. Finally, this article combines the improved algorithm to construct a simulated annealing neural network algorithm and builds a vocational education coursework assessment result prediction system, which verifies the prediction effect and assessment effect of this system through experimental research.